A Multicenter, Placebo‐Controlled, Double‐Blind, Randomized Study of Efficacy and Safety of Ocinaplon (DOV 273,547) in Generalized Anxiety Disorder - Czobor, Pál (CNS Neurosci Ther, 2009)
Preclinical studies demonstrated that ocinaplon, a positive allosteric modulator of GABA(A) receptors, possesses anxiolytic‐like actions at doses devoid of the side effects typically associated with benzodiazepines. The aim of this study was to evaluate the effects of ocinaplon in a multicenter, double‐blind proof‐of‐concept trial of male and female outpatients who met DSM‐IV criteria for GAD with no coexisting depression, and had a baseline score of ≥20 on the Hamilton Scale for Anxiety (HAM‐A). Patients with <20% reduction in HAM‐A to placebo in a single‐blind 7‐day run‐in period were randomly assigned to treatment with ocinaplon 90 mg t.i.d. (n = 31) or placebo for 28 days (n = 29). Ocinaplon was more effective than placebo in reducing HAM‐A scores (P= 0.009). Patients assigned to ocinaplon exhibited a mean improvement of 14.2 points (SE = 2.6) on the total score of the HAM‐A scale at the conclusion of the trial, while patients assigned to placebo obtained a mean improvement of 6.3 points (SE = 2.0). A significant (P= 0.023) difference in improvement between ocinaplon and placebo was observed beginning at and continuing from 1‐week after the initiation of dosing. The proportion of patients with treatment‐emergent adverse events (TEAE) was not statistically significant between ocinaplon and placebo. One serious adverse event (SAE) occurred in the ocinaplon group that was considered possibly related to study medication (icterus following transaminase elevations). The patient had preexisting medical conditions that may have contributed to this SAE. A full recovery was observed with no residual effects. The overall safety profile revealed no patterns of TEAEs, including those effects typically associated with other anxiolytic and/or benzodiazepine compounds, such as sedation. Ocinaplon appears to be a well‐tolerated and effective treatment for GAD. It produces a rapid onset of anxiolytic action absent the side effects (e.g., dizziness, sedation) typically reported following anxiolytic doses of benzodiazepines.